INTERDEPENDENCE AND NETWORK OVERSIGHT IN 1990S INTERNET GOVERNANCE - Grosse, Meghan (AoIR Selected Papers of Internet Research, 2021)
In October 2016, the contract between the United States Department of Commerce and the Internet Corporation for Assigned Names and Numbers (ICANN) officially expired. This contract represented a long-standing and close relationship between the United States government and ICANN, a relationship that positioned the U.S. as a kind of linchpin in determining the shape and coordination of the global, extraterritorial internet. This research seeks to address the question: what interests and values shaped ICANN at the time of its establishment and in what ways do debates about this system reflect broader concerns about the U.S.-centric nature of early internet governance policy? I address this question using archival analysis focusing on the Ira Magaziner Electronic Commerce papers at the Clinton Presidential Library in Little Rock, Arkansas. In examining this archive, there are repeated concerns about the U.S.-centric nature of early internet governance policy, concerns that were clear as early as the mid-1990s and which remained at issue with the oversight of ICANN until 2016. While espousing the values of competitive free-market, the internet governance policy promoted by the U.S. government during the Clinton Administration raised concerns about the concentration of power and potentially monopolistic control of the network by a single nation. Understanding the foundations of debates around oversight and multistakeholderism that took place as early as the 1990s helps us better understand more recent changes in internet governance and also help contextualize and ground discussions about how to best create a truly representative global internet in the future.